A rapid method for separating and concentration of food-borne pathogens using elution from ready-to-eat vegetables - Rajabzadeh, Safieh (Iran J Microbiol, 2018)
BACKGROUND AND OBJECTIVES: Traditional culture methods for detection of food-borne pathogens, a major public health problem, are simple, easily adaptable and very practical, but they can be laborious and time consuming. In this study, we eliminated culturing steps by developing a new separation method and therefore, decreased the detection time of food-borne pathogens (Salmonella enterica serovar Typhimurium, Escherichia coli O157:H7 and Listeria monocytogenes) to a few hours. MATERIALS AND METHODS: We used alkaline water and different alkaline buffers to elute bacteria from the lettuce surface as a model for ready-to-eat vegetables. Buffers used were as follows: 1) 0.05 M glycine; 2) 0.05 M glycine −100 mM Tris base −1% (w/v) beef extract; 3) buffer peptone water; 4) buffer phosphate saline. Buffers were adjusted to pH of 9, 9.5 and 10. In order to elute the bacteria, the lettuce pieces were suspended into buffers and shacked for 30, 45 and 60 min. Moreover, a multiplex PCR method for the simultaneous detection of food-borne pathogens was performed. RESULTS: The results showed that buffer peptone water at pH 9.5 for 45 min have high ability to elute bacteria from the lettuce surface and the bacteria can be detected using multiplex PCR. CONCLUSION: We developed a new rapid and efficient method for simultaneous separation of food-borne pathogens. This method eliminates culturing stages and permits the detection and identification of target pathogens in a few hours.